EFEKTIFITAS PENYULUHAN PADA PT. TAKII SEED TERHADAP PETANI KOOL DI DESA PIKATAN, KECAMATAN WONODADI, KABUPATEN BLITAR - EKO MURDIYANTO (Universitas Sebelas Maret, 2011)
Agriculture extension workers as a source of innovation must have good communication skills in spreading innovations to farmers. Field extension as a controller extension activities are a source of innovation information. Therefore, communication skills will affect the extension methods that are used to fit the target farmers and extension successes. Therefore PT. TAKII SEED in developing cabbage TI 157 need to develop models that can be accepted by farmers in the Pikatan village. In the counseling process, PT. TAKII SEED collaboration with UD TANI MAKMUR as a provider field asistant. Extension method used the method of audio-visual methods, Farmer Meeting method, and Farmer Field Day method.